CD4(+)CD25(+)Foxp3(+) regulatory T cells induce alternative activation of human monocytes/macrophages - Tiemessen, Machteld M. (National Academy of Sciences, 2007)
CD4(+)CD25(+)Foxp3(+) regulatory T cells (Tregs) are potent suppressors of the adaptive immune system, but their effects on innate immune cells are less well known. Here we demonstrate a previously uncharacterized function of Tregs, namely their ability to steer monocyte differentiation toward alternatively activated macrophages (AAM). AAM are cells with strong antiinflammatory potential involved in immune regulation, tissue remodeling, parasite killing, and tumor promotion. We show that, after coculture with Tregs, monocytes/macrophages display typical features of AAM, including up-regulated expression of CD206 (macrophage mannose receptor) and CD163 (hemoglobin scavenger receptor), an increased production of CCL18, and an enhanced phagocytic capacity. In addition, the monocytes/macrophages have reduced expression of HLA-DR and a strongly reduced capacity to respond to LPS in terms of proinflammatory mediator production (IL-1β, IL-6, IL-8, MIP-1α, TNF-α), NFκB activation, and tyrosine phosphorylation. Mechanistic studies reveal that CD4(+)CD25(+)CD127(low)Foxp3(+) Tregs produce IL-10, IL-4, and IL-13 and that these cytokines are the critical factors involved in the suppression of the proinflammatory cytokine response. In contrast, the Treg-mediated induction of CD206 is entirely cytokine-independent, whereas the up-regulation of CD163, CCL18, and phagocytosis are (partly) dependent on IL-10 but not on IL-4/IL-13. Together these data demonstrate a previously unrecognized function of CD4(+)CD25(+)Foxp3(+) Tregs, namely their ability to induce alternative activation of monocytes/macrophages. Moreover, the data suggest that the Treg-mediated induction of AAM partly involves a novel, cytokine-independent pathway.